Synthesis of research report of personnel: Case study on Faculty of Education, Mahasarakham University - Rungthip Singporn; Prasart Nuangchalerm (Journal of Education and Learning (EduLearn), 2021)
The purpose of this research was to synthesize research report of personnel in the Faculty of Education, Mahasarakham University. There were 81 research reports funded by Faculty of Education, Mahasarakham University between the academic years of 2012-2019 were employed. The research revealed that most of research concerning teacher development amounting to 69 researches, followed by research report of the support staff amounting to 12 researches. Most of research reports were basic research, applied research, and collaborative teaching research amounting to 55 researches, followed by production research and development of personnel that emphasized on the concept of learning based on the actual situation amounting to 11 researches. The greatest number of research was produced and published in 2018, 23 researches, and in 2019, 13 researches. They were publishing in Thai journals, total of 75 research. The utilization of research to apply for policy benefits, 75 research and for public in four research. Research methodology employed 50 operational researches, 29 quasi-experimental researches, 33 researches to studies, 25 comparative researches and 16 researches to find correlation.